2021
DOI: 10.1002/jcc.26718
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of group 14 elements in sp3 and sp2 environment by fragment structure energy analysis

Abstract: To explore the characteristics of group 14 elements in sp3 and sp2 hybrid environments systematically, the concept of fragment structure energy (FSE) was proposed through ab initio molecular orbital method. A fragment in this study means a building block of molecular structure and the energy of each kind of fragments (FSE) is obtained from the total electronic energy of different size of model compounds by just a simple algebraic method. The model compounds are the hydrogen‐terminated diamond and graphene anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For comparison, the energy gap of diamond-type molecules with molecular sizes similar to those of dodecahedranes is also shown in Table 3 as the model of silicon carbide. C 30 H 40 and Si 30 H 40 are the model compounds of the diamond-type crystal terminated by hydrogens and the silicon analogue, respectively, while C 10 Si 20 H 40 and C 20 Si 10 H 40 are the two types of Si/C mixed congeners [ 31 ]. The frontier molecular orbitals of the seven isomers a to f , dodecahedrane, and persiladodecahedrane are displayed in Figures S2–S10 of the Supplementary Materials .…”
Section: Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the energy gap of diamond-type molecules with molecular sizes similar to those of dodecahedranes is also shown in Table 3 as the model of silicon carbide. C 30 H 40 and Si 30 H 40 are the model compounds of the diamond-type crystal terminated by hydrogens and the silicon analogue, respectively, while C 10 Si 20 H 40 and C 20 Si 10 H 40 are the two types of Si/C mixed congeners [ 31 ]. The frontier molecular orbitals of the seven isomers a to f , dodecahedrane, and persiladodecahedrane are displayed in Figures S2–S10 of the Supplementary Materials .…”
Section: Structuresmentioning
confidence: 99%
“…However, there are only a few theoretical studies for two-element-mixing analogues of tetrahedrane and cubane [ 29 , 30 ]. In this situation, our fragment structure energy (FSE) analysis demonstrated that Si/C alternately mixing contributes to the stabilization of the systems in the ideal (with no angle strain) sp 3 environment as well as the sp 2 environment, which was not observed for the mixing of carbon or the other heavier group 14 elements [ 31 ].…”
Section: Introductionmentioning
confidence: 99%